Evidence of direct cell-cell fusion in Borrelia by cryogenic electron tomography - Kudryashev, Mikhail; Cyrklaff, Marek; Alex, Björn; Lemgruber, Leandro; Baumeister, Wolfgang; Wallich, Reinhard; Frischknecht, Friedrich (Cellular microbiology, 2011)
Some Borrelia species are the causative agents of tick-borne Lyme disease responsible for different disabilities depending on species and hosts. Borrelia are highly motile bacterial cells, and light microscopy shows that these spirochetes can associate with each other during movement. Using cryo-electron tomography, we observed closely associated Borrelia cells. Some of these showed a single outer membrane surrounding two longitudinally arranged cytoplasmic cylinders. We also observed fusion of two cytoplasmic cylinders and differences in the surface layer density of fused spirochetes. These processes could play a role in the interaction of Borrelia species with the host's immune system.